الحماية الجزائية للمستهلك في التشريع الجزائري - رضا سماعلي (My University, 2021)
Summary: Consumer protection occupies an important part of the Algerian legislature's concerns, as it relates to several legal norms guaranteeing such protection and penalizing any interference in the production process. natural or moral person - for any breach of a legitimate consumer right or any defective product that may pose a threat to the security of the areas or the safety of the consumer, However, consumer damage was not expected to occur in order to introduce such sanctions, but the legislature was concerned with the early detection of such abuses and risks before they reached the consumer; Through the establishment of regulatory structures and the granting of powers to administrative bodies to operationalize the protective and even deterrent role authorized by law, the legislature also authorized civil society to participate in the provision of consumer protection through consumer protection associations authorized to represent consumers before several administrative bodies and before the judiciary; Establishment as a civil party in the event of any consumer damage caused by a defective product. .................. ملخص : تحتل حماية المستهلك جيزا هاما من اهتمامات المشرع الجزائري، فقد خصه بعديد القواعد القانونية التي تكفل هذه الحماية وترتب جزاءات على أي متدخل في عملية الإنتاج، شخصا طبيعيا كان أم معنويا- عن كل إخلال بحق من الحقوق المشروعة للمستهلك، أو عن أي منتوج معيب قد يشكل خطرا على أمن المجالات أو سلامة المستهلك، إلا أنه لا يُنتظر حدوث الضرر على المستهلك لتوقيع هذه الجزاءات وإنما اهتم المشرع بالكشف المبكر عن هذه التجاوزات والأخطار قبل وصولها إلى المستهلك؛ وذلك عن طريق انشاء هياكل رقابية ومنح صلاحيات لهيئات إدارية لتفعيل الدور الوقائي الحمائي وحتى الردعي في التي أجازها لها القانون، كما أجاز المشرع للمجتمع المدني المشاركة في توفير الحماية للمستهلك وذلك عن طريق جمعيات حماية المستهلك التي فوّض لها أمر تمثيل المستهلك أمام عديد الهيئات الإدارية، وأمام القضاء؛ والتأسيس كطرف مدني في حال حدوث أي ضرر بالمستهلك نجم عن أحد المنتوجات المعيبة. ................. Résumé : La protection des consommateurs occupe une part importante des préoccupations du législateur algérien, car elle concerne plusieurs normes juridiques garantissant cette protection et sanctionnant toute ingérence dans le processus de production. personne physique ou morale - pour toute violation d’un droit légitime du consommateur ou de tout produit défectueux qui peut constituer une menace pour la sécurité des zones ou la sécurité du consommateur, Cependant, le dommage au consommateur ne devrait pas se produire afin d’introduire de telles sanctions, mais le législateur s’est préoccupé de la détection précoce de tels abus et risques avant qu’ils n’atteignent le consommateur; Par la mise en place de structures réglementaires et l’octroi de pouvoirs aux organes administratifs pour opérationnaliser le rôle protecteur et même dissuasif autorisé par la loi, le législateur a également autorisé la société civile à participer à la protection des consommateurs par l’intermédiaire d’associations de protection des consommateurs autorisées à représenter les consommateurs devant plusieurs organes administratifs et devant le pouvoir judiciaire; Établissement en tant que partie civile en cas de dommages causés par un produit défectueux.